Neurocysticercosis presenting as focal hydrocephalus - Malik, Azharuddin Mohammed (BMJ Publishing Group, 2014)
A 40-year-old man presented with a 2-month history of headache, nausea and vomiting, with generalised seizures for the past 15 days. On examination he had bilateral papilloedema, visual acuity was 6/6 in both eyes but perimetry showed right homonymous inferior quadrantanopia. His MRI showed numerous small cystic lesions with eccentric nodules, diffusely distributed in bilateral cerebral and cerebellar hemispheres. There was also focal hydrocephalus involving occipital and temporal horns of the left lateral ventricle leading to its selective dilation. Stool examination showed ova of Taenia solium. He was treated with albendazole, prednisone and sustained release sodium valproate for 1 month. His headache resolved and he is free of seizures. Repeat perimetry at 1 month also showed resolution of visual field defect.